Lexin på Island? Funderingar kring isländska invandrarordböcker - Svavarsdóttir, Ásta (LexicoNordica, 1999)
The main subject of the artic le is a pilot-project canied out at the Institute of Lexicography in Reykjavfk, lceland. The purpose of the project was to investigate the practi cality of translating and adjusting the Swedish LEXIN-material fo r use as a base for bilingual dictionari es for fo reign immigrants in iceland, much like the original Swedi sh material has been used for decades in Sweden. The possibility of using the translations already made for the Swedi sh bilingual dictionaries for their Icelandic counterparts was also evaluated. In the investigation, the main emphasis was put on two questions: (1) What is the proportion of absolute equi valents in the Swedish and Icelandic word li sts? (2) Does the adoption of the Swedish material yield an lcelandic word list that is representative enough for the vocabulary of lcelandic? The answer of the first question is important with respect to the use of translations toa third language as direct equi valency is a prerequi site for their usage. The result of this part was satisfacto ry as the proportion proved to be 60-70%. In order to seek an answer to the second question, the vocabulary appearing in the Icelandic LEXIN-translation was compared to two original Icclandic word li sts compiled on the basis of frcqucncy. The result of the comparison was that 50--70% of the words in the Icelandic li sts were represented in the LEXIN-translation and the di fference to a great part being cxplainable by specific lcelandic and Swedish vocabulary.